Dopaminergic control of cognitive flexibility in humans and animals - Klanker, Marianne; Feenstra, Matthijs; Denys, Damiaan (Frontiers in Neuroscience, 2013)
Striatal dopamine is thought to code for learned associations between cues and reinforcers and to mediate approach behavior towards a reward. Less is known about the contribution of dopamine to cognitive flexibility – the ability to adapt behavior in response to changes in the environment. Altered reward processing and impairments in cognitive flexibility are observed in psychiatric disorders such as obsessive compulsive disorder. Patients with this disorder show a disruption of functioning in the frontostriatal circuit and alterations in dopamine signaling. In this review we summarize findings from animal and human studies that have investigated the involvement of striatal dopamine in cognitive flexibility. These findings may provide a better understanding of the role of dopaminergic dysfunction in cognitive inflexibility in psychiatric disorders, such as OCD.